The effects of cognitive behavioral therapy in women with polycystic ovary syndrome: A meta-analysis - Tang, Rong; Yang, Junlan; Yu, Yanmei; Fang, Yuying (Frontiers in Psychology, 2022)
Abstract Background Cognitive behavioral therapy (CBT) has well characterized benefits in alleviating diseases associated depression, anxiety and obesity, resulting in a marked improvement of patient’s quality of life. There are some studies regarding the effects of CBT on patients with polycystic ovary syndrome (PCOS). However, there is still no report of a meta-analysis for systematic assessment. Objectives To evaluate the effectiveness of CBT in improving weight loss, anxiety, depression, life quality, compliance and pregnancy outcomes in patients with PCOS. Methods Studies regarding CBT related to PCOS in PubMed, Cochrane library, Embase, ClinicalTrials.gov, CNKI, WANFANG DATA were searched for up to November 19, 2020. A random-effect model was used to perform a meta-analysis. Results Eight trials regarding CBT compared with lifestyle modification and routine treatments were included. No differences in depression (SMD -1.11; 95%CI -2.28, 0.07; P>0.05), BMI (SMD 0.88; 95%CI -0.94, 2.71; P>0.05) or overall life quality (SMD 1.24; 95% CI -0.44, 2.92; P>0.05) were evident between CBT and control groups; however, anxiety (SMD -1.12; 95% CI -2.1, -0.13; P<0.05) and quality of life in hirsutism (SMD 0.92; 95%CI 0.48, 1.35; P<0.05) were significantly improved. For secondary outcomes, both patient compliance and pregnancy rate were improved, but no significant change in pregnancy loss rate was identified. Conclusions CBT exhibited obvious advantages in alleviation of anxiety, improvement of quality of life in hirsutism and the increase of compliance and pregnancy rate in patients with PCOS. Larger and higher-quality randomized controlled trials are needed to clarify the role of CBT in PCOS.